Samuel Johnson and the powers of friendship - Cousins, A. D., 1950-; Derrin, Daniel, 1980-; Napton, Dani (New York, NY : Routledge, 2024)
"This book is the first to assess Johnson's diverse insights into friendship-that is to say, his profound as well as widely ranging appreciation of it-over the course of his long literary career. It examines his engagements with ancient philosophies of friendship and with subsequent reformulations of or departures from that diverse inheritance. The volume explores and illuminates Johnson's understanding of friendship in the private and public spheres-in particular, friendship's therapeutic amelioration of personal experience and transformative impact upon civil life. Doing so, it considers both his portrayals of interaction with his friends, and his more overtly fictional representations of friendship, across the many genres in which he wrote. It presents at once an original re-assessment of Johnson's writings and new interpretations of friendship as an element of civility in mid-eighteenth century British culture"--
Introduction / A.D. Cousins -- Johnson, friendship and politics / Nicholas Hudson -- 'The friend of goodness' : Johnson and the 'Life of Savage' / Julie Crane -- Intimate benevolence : friendship in Johnson's periodical essays / Paul Tankard -- Johnson's friendships with women / Norma Clarke -- Friendships in prison : Imlac, Rasselas, the Hermit and the Astronomer / A. D. Cousins -- Friendship, societas, and analysis of Scotland's highlands and islands / Daniel Derrin -- Critical friendships in the Lives of the Poets / Philip Smallwood -- Seeking minds in unison : Johnson and his friends in the Letters / Pat Rogers -- Recent studies on Johnson and friendship / Dani Napton.
Keywords: Johnson, Samuel, -- 1709-1784 -- Criticism and interpretation; Johnson, Samuel, -- 1709-1784 -- Friends and associates; Friendship in literature; English literature -- 18th century -- History and criticism; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; LITERARY CRITICISM / Poetry